Phosphobacteria inoculation enhances the benefit of P–fertilization on Lolium perenne in soils contrasting in P–availability. (September 2019) - Barra, Patricio Javier; Pontigo, Sofia; Delgado, Mabel; Parra–Almuna, Leyla; Duran, Paola; Valentine, Alexander Joseph; Jorquera, Milko Alberto; Mora, María de la Luz
Abstract: Phosphorus (P) is an essential macronutrient for plant growth and is therefore an important component of agricultural fertilizers, especially for P–deficient soils. As a more environmentally friendly alternative to P–fertilization, phosphobacteria are regularly being proposed as bio–inoculants for plants that are cultivated in P–deficient soils. Although it is known that phosphobacteria inoculation can influence the growth and P nutrition of the host plant, the underlying responses at the molecular level have to date, not been fully elucidated. Here, we evaluated the single and combined effects of a phosphobacteria consortium inoculation and triple superphosphate fertilization on the biomass, P content, anti–oxidant capacity and phosphate–transporters genes of Lolium perenne . Plants were grown over 45 days in presence and absence of P–fertilization and phosphobacteria inoculation in two soils with different P bio–availabilities. Our results reveal that irrespective of P–availability in soils, the phosphobacteria inoculation provides an 'enhancement effect' of the P–fertilization on the development, nutrition and the alleviation of oxidative stress, in L. perenne . This was evidenced by higher biomass, increased P content, and lower cellular damage in tissues of the inoculated plants. The inoculation with phosphobacteria decreased the relative gene expression of superoxide dismutase isoforms in tissues of fertilized plants grown in the P–deficient soil. In addition, phosphobacteria inoculation was also associated with a lower relative expression of phosphate–transporter genes of P–fertilized plants. Therefore, instead of being an alternative to P–fertilization, phosphobacteria could rather be a promising complement to P–fertilization in P–deficient soils and potentially reduce fertilizer application rates. Based on our findings, an explicatory model of plant–soil–phosphobacteria interactions on the regulation of anti–oxidant and phosphate–transport capacities in P–deficient, is proposed. Highlights: Phosphobacteria enhanced biomass and P‒content in plants grown in P‒fertilized soils. Phosphobacteria decreased lipid peroxidation in plants grown in P‒fertilized soils. Phosphobacteria decreased P‒transporter gene expression in P‒fertilized plants. Phosphobacteria decreased SOD isoforms gene expression in P‒fertilized plants. Phosphobacteria inoculation enhanced the beneficial effect of P‒fertilization.